Effect of in situ phases on microstructure and properties in Al–Bi immiscible alloy. Issue 12 (12th August 2020) - Man, Tiannan; Xiang, Zhaolong; Zhang, Lin; Wang, Engang
Abstract : Al–Bi immiscible alloy is of particular interest as potential self-lubricating wear materials with a homogeneous distribution of minority phase. However, it is difficult to obtain a homogeneous microstructure by conventional casting methods due to liquid phase separation of Al–Bi immiscible alloy. We have developed a new strategy to restrain liquid phase separation and improve the properties of Al–Bi immiscible alloy by in situ phases. The in situ AlB2 phase acts as heterogeneous nucleation site to accelerate the nucleation and slow down the velocity of the Bi-rich droplet, resulting in a significant size reduction and a homogeneous microstructure of Al–Bi immiscible alloy. The self-lubricating wear resistance of Al–Bi immiscible alloy can be further enhanced by in situ Al2 Cuphase.